River Microbiome Composition Reflects Macroscale Climatic and Geomorphic Differences in Headwater Streams - URycki, Dawn R.; Good, Stephen P.; Crump, Byron C.; Chadwick, Jessica; Jones, Gerrad D. (Frontiers in Water, 2020)
Maintaining the quality and quantity of water resources in light of complex changes in climate, human land use, and ecosystem composition requires detailed understanding of ecohydrologic function within catchments, yet monitoring relevant upstream characteristics can be challenging. In this study, we investigate how variability in riverine microbial communities can be used to monitor the climate, geomorphology, land-cover, and human development of watersheds. We collected streamwater eDNA and used 16S rRNA sequencing to profile microbiomes from headwaters to outlets of the Willamette and Deschutes basins, two large watersheds prototypical of Pacific Northwest region of the United States. Within each watershed, microbial community composition correlated strongly (mean Mantel test statistic r = 0.24 in Willamette, 0.17 in Deschutes) with development-related characteristics, including percentage impervious area and percentage of low, medium, and high density developed area. In the temperate Willamette basin, percentage of forest and shrublands (r = 0.34) and percentage of medium density developed area (r = 0.30) were among the strongest correlates with microbial community composition. In the arid Deschutes basin, however, geomorphic characteristics were the most strongly correlated to microbial community composition (e.g., r = 0.33 for topographic index, 0.29 for topographic relief). In headwater sub-catchments across both watersheds, microbial community assemblages correlated with catchment-scale climate and geomorphology (r = 0.45 and 0.23, respectively), but these relationships were weaker downstream. Our results build on previous work relating the streamwater microbiome to hydrologic regime and demonstrate that microbial eDNA in headwater streams additionally reflects the structural configuration of landscapes as well as other natural and anthropogenic processes upstream. Our results offer an encouraging indication that streamwater eDNA carries information not only about microbial ecology, but also can be a useful tool for monitoring multiple upstream watershed characteristics.